RESPON VARIETAS TANAMAN SAWI (Brassica juncea L.) TERHADAP LARUTAN HARA (AB MIX) PADA SISTEM HIDROPONIK - Istiqamah, Annisa; Rauf, Abdul; Aiyen, Aiyen (AGROTEKBIS, 2016)
The research aimed to discover the response of growth and production of two mustard varieties on substrate hydroponic system and the concentration of AB Mix solution on each variety. The research was conducted in January to March 2016, in Green House, Faculty of Agriculture, Tadulako University by using Split Plot Design. The main plot was Tosakan and Shinta varieties, while the subplot was concentration of AB Mix nutrient solution, such as 4 ml/L of water, 5 ml/L of water, 6 ml/L of water and 7 ml/L of water. The research shows that nutrient solution is very good generally to support the production of mustard on a hydroponic substrate. Tosakan variety has better response than Shinta variety. Varieties and concentration of nutrion solution have interaction, the concentration of nutrient solution that was good for Tosakan variety is 6 ml/L, it was representedÂ by the leafs number were more in all plants age, the its leafs were wider, canopy and root (fresh and dry)Â were heavier, while Shinta variety of the concentration of nutrient solution 4-7 ml / L resulted the production were not significantly different.Â Key Words: Mustard, nutrient solution, substrate hydroponic.